An integrated model with stable numerical methods for fractured underground gas storage. (20th March 2023) - Xue, Wendi; Wang, Yi; Chen, Zhe; Liu, Hang
Abstract: Underground gas storage formed from the depleted oil/gas reservoir has excellent development potential for storing a large amount of natural gas. However, the reservoir in some regions is mostly a fractured structure. Its pore distribution and permeability theory are complex. An integrated model for the fractured underground gas storage (UGS) formed from the depleted oil/gas reservoir is proposed for the first time to respond to the absence of the numerical model. This integrated model couples the wellbore, reservoir and gas properties. We propose a gas flow direction factor and transient heat transfer models for the alternative flow directions in the wellbore. Natural gas property models are adopted to describe gas properties more accurately. We analyze the stability, efficiency and global mass conservation of the reservoir model. A new equation for source term is proposed to solve the reservoir model stably and efficiently. A pressure correction method is proposed to guarantee global mass conservation for long period operation of the UGS. Our simulation results indicate that the new equation for the source term ultimately ensures diagonal dominance and improves 20%–30% computational efficiency. The pressure correction method strictly guarantees global mass conservation. By simulating the entire cycle of gas injection, wellbore shutdown and gas production, we determine the maximum gas storage capacity of the UGS and analyze the variation law of pressure and temperature in the wellbore and reservoir. Highlights: An integrated model for fractured underground gas storage is proposed. A stable and global mass conservative numerical method is proposed for solving the model. The operation of UGS are studied by simulating the entire cycle of gas injection, wellbore shutdown, and gas production.